Everyday life in mass dictatorship : collusion and evasion - Lüdtke, Alf, 1943-2019 1943-2019 Herausgeber (Mass dictatorship in the twentieth century, 2016)
"Dictatorship implies oppression and arbitrary violence from above. However, this volume and the Mass Dictatorship in the 20th Century series to which it contributes dismantles that general assumption. Everyday Life in Mass Dictatorship explores the multiple forms and practices of ordinary people as they became active participants in the grand mobilisation of society not only promised, but actively pursued by dictatorial regimes in the 20th century. The volume is centrally concerned with two aspects of collusion and evasion: warfare and ruthless policies of exclusion. The impact this avalanche of unbounded violence had on survivors and successive generations is the overarching theme of the studies presented in this volume on post-colonial and post-Stalinist dictatorships. The extent to which post-colonial regimes carried on non-democratic asymmetries of power or established them anew is breathtaking. Yet the prospects of better living and 'modern times' met with overwhelming popular support in the East and West, as well as in the global North and South"--